A world‐wide analysis of reduced sensitivity to DMI fungicides in the banana pathogen Pseudocercospora fijiensis. Issue 7 (10th April 2021) - Chong, Pablo; Essoh, Josué Ngando; Arango Isaza, Rafael E; Keizer, Paul; Stergiopoulos, Ioannis; Seidl, Michael F; Guzman, Mauricio; Sandoval, Jorge; Verweij, Paul E; Scalliet, Gabriel; Sierotzski, Helge; de Lapeyre de Bellaire, Luc; et al.
Abstract: BACKGROUND: Pseudocercospora fijiensis is the causal agent of the black leaf streak disease (BLSD) of banana. Bananas are important global export commodities and a major staple food. Their susceptibility to BLSD pushes disease management towards excessive fungicide use, largely relying on multisite inhibitors and sterol demethylation inhibitors (DMIs). These fungicides are ubiquitous in plant disease control, targeting the CYP51 enzyme. We examined sensitivity to DMIs in P . fijiensis field isolates collected from various major banana production zones in Colombia, Costa Rica, Dominican Republic, Ecuador, the Philippines, Guadalupe, Martinique and Cameroon and determined the underlying genetic reasons for the observed phenotypes. RESULTS: We observed a continuous range of sensitivity towards the DMI fungicides difenoconazole, epoxiconazole and propiconazole with clear cross‐sensitivity. Sequence analyses of PfCYP51 in 266 isolates showed 28 independent amino acid substitutions, nine of which correlated with reduced sensitivity to DMIs. In addition to the mutations, we observed up to six insertions in the Pfcyp51 promoter. Such promoter insertions contain repeated elements with a palindromic core and correlate with the enhanced expression of Pfcyp51 and hence with reduced DMI sensitivity. Wild‐type isolates from unsprayed bananas fields did not contain any promoter insertions. CONCLUSION: The presented data significantly contribute to understanding of the evolution and global distribution of DMI resistance mechanisms in P . fijiensis field populations and facilitate the prediction of different DMI efficacy. The overall reduced DMI sensitivity calls for the deployment of a wider range of solutions for sustainable control of this major banana disease. © 2021 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Studies on Pseudocercospora fijiensis demethylation inhibitor (DMI) sensitivity shows that Pfcyp51 modulations correlated with fungicide resistance. The importance of amino acid substitutions at positions 137, 311, 378, 379 and 458–461 is strengthened by mathematical modelling. Changes in these positions compromise the three‐dimensional structure of the protein resulting in an affinity change. The presence of repeated elements and insertions in the promotor region of Pfcyp51 was also positively correlated with resistance to DMIs. © 2021 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.